Transition Process of Brazilian mothers residing in Japan to raising children with developmental disorders within the Japanese healthcare and welfare - Asano, Izumi; Yanagisawa, Satoko (Kokusai Hoken Iryo (Journal of International Health), 2022)
Objectives  To clarify the transition process of Brazilian mothers of children with developmental disorders residing in Japan from “mothers raising healthy children” to “mothers raising children with developmental disorders within the Japanese healthcare and welfare system.”Methods  We conducted semi-structured interviews of 11 Brazilian mothers who raised their children for at least 1 year after the children were diagnosed having developmental disabilities.According to an interview guide we prepared, the mothers were requested to talk regarding raising their children and treatment and education after they suspected that their children had developmental disabilities and regarding the changes in their views about the same. The interviews were analyzed using a modified Grounded Theory Approach (M-GTA).Results and discussions  The average age of the research participants was 37.4 years. The children’s age ranged between 2 to 8 years. All the children had an autism spectrum disorder.   Mothers began «suspecting» that their children exhibited developmental problems around the age of 1.5 years. Some mothers experienced a sense of «diving into turmoil» when diagnosis of autism was given. Since before the diagnosis, mothers experienced a persistent and «ongoing emotional pain due to their children’s disorder». Meeting people they can trust «provided them with the support to become stronger», and were ready to do anything for their children; in other words, they became akin to [superwomen for their children].  This process was similar to that observed in a previous study involving Japanese mothers. A short time between the initial suspicion of their children’s development and the first clinical examination and taking actions toward a diagnosis, in other words, “impatience,” were characteristics of Brazilians mothers.Conclusions  The transition process of Brazilians mothers was similar to that of Japanese mothers, with some distinct characteristics. Managing impatience, providing intervention after a diagnosis, and seeking support from others will promote this transition.